2016
DOI: 10.3892/br.2016.720
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of bromelain in clinical and therapeutic applications

Abstract: Pineapple has been used as part of traditional folk medicine since ancient times and it continues to be present in various herbal preparations. Bromelain is a complex mixture of protease extracted from the fruit or stem of the pineapple plant. Although the complete molecular mechanism of action of bromelain has not been completely identified, bromelain gained universal acceptability as a phytotherapeutic agent due to its history of safe use and lack of side effects. Bromelain is widely administered for its wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
164
0
20

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(186 citation statements)
references
References 76 publications
(57 reference statements)
2
164
0
20
Order By: Relevance
“…La presencia de proteínas que la literatura reporta para cereales son tipo: albúmina, globulinas, prolaminas, glutelinas según Cavazos y Gonzales (2013) y la Canaryseed Development Commission of Saskatchewan (2014) refiere que estas proteínas son deficientes en lisina, pero ricos en cisteina, triptófano y fenilalanina y arginina, siendo moléculas adecuadas para la acción de una glicoproteína, una enzima proteolítica tipo cisteinproteasa llamada bromelina, presente en Ananás comosus y que ejerce su actividad en un intervalo de pH 4,5 a 9,5. (Benítez et al (2008), Scopes (2013, Arnon y Shapira (1967); Hale et al (2005) citados por: Rathnavelu et al, 2016). De lo expuesto se infiere que las moléculas resultantes de la mezcla estarían en estado de hidrólisis, formando péptidos pequeños dada la riqueza de aminoácidos de corte para esta enzima y en forma de sales en la solución acuosa y se evidencia esto en la prueba negativa para proteínas en el extracto de diclorometano.…”
Section: Resultados Y Discusiónunclassified
“…La presencia de proteínas que la literatura reporta para cereales son tipo: albúmina, globulinas, prolaminas, glutelinas según Cavazos y Gonzales (2013) y la Canaryseed Development Commission of Saskatchewan (2014) refiere que estas proteínas son deficientes en lisina, pero ricos en cisteina, triptófano y fenilalanina y arginina, siendo moléculas adecuadas para la acción de una glicoproteína, una enzima proteolítica tipo cisteinproteasa llamada bromelina, presente en Ananás comosus y que ejerce su actividad en un intervalo de pH 4,5 a 9,5. (Benítez et al (2008), Scopes (2013, Arnon y Shapira (1967); Hale et al (2005) citados por: Rathnavelu et al, 2016). De lo expuesto se infiere que las moléculas resultantes de la mezcla estarían en estado de hidrólisis, formando péptidos pequeños dada la riqueza de aminoácidos de corte para esta enzima y en forma de sales en la solución acuosa y se evidencia esto en la prueba negativa para proteínas en el extracto de diclorometano.…”
Section: Resultados Y Discusiónunclassified
“…In this context, Bromelain has been documented to increase blood and urine levels of several antibiotics in humans such as amoxicillin and levofloxacin [17,50,51]. A combined bromelain and antibiotic therapy was shown to be more effective than antibiotics alone in treating pyelonephritis, urinary tract infections, pneumonia, bronchitis, sinusitis, cutaneous Staphylococcus infection, thrombophlebitis, and perirectal and rectal abscesses [13,14,52]. A combination of bromelain, serenoa repens, lycopene, and selenium has been administered as an adjuvant therapy in combination with levofloxacin for patients with chronic bacterial prostatitis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Saita et al [29] reported an expulsion success rate of 68 and 81% in patients with an average stone size of 12 mm treated with nifedipine and prednisolone or prednisolone alone respectively. Contrary to the steroids, bromelain has a history of safe use and lack of side effects, and thus has acquired a reputation of acceptability [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations